Bone marrow transplantation improves hepatic fibrosis in Abcb4−/− mice via Th1 response and matrix metalloproteinase activity. Issue 6 (25th August 2011) - Roderfeld, Martin; Rath, Timo; Pasupuleti, Sravanthi; Zimmermann, Marc; Neumann, Caterina; Churin, Yuri; Dierkes, Christian; Voswinckel, Robert; Barth, Peter J; Zahner, Daniel; Graf, Jürgen; Roeb, Elke
Abstract : Objective: Reports on the effects of bone marrow-derived cells on hepatic fibrosis are contradictory. Impaired fibrosis but increased inflammation has recently been demonstrated 10 weeks after bone marrow transplantation (BM-Tx) in Abcb4 −/− mice. It is hypothesised that BM-Tx might have long-term therapeutic potential by altering the immunological and matrix remodelling processes leading to hepatic regeneration. Methods: After lethal irradiation of recipient mice, BM cells from GFP+ donor mice (allogeneic Tx) or Abcb4 −/− mice (syngeneic Tx) were transplanted via tail vein injection. Readouts were performed 2, 10 and 20 weeks after Tx. Liver integrity was assessed serologically and histologically. Surrogate markers for fibrogenesis, T helper (Th) response, inflammation, graft-versus-host disease and fibrolysis were analysed by quantitative real-time PCR, zymography and immunohistology. Results: 20 weeks after syngeneic and allogeneic BM-Tx, hepatic grading and staging were significantly improved. In contrast, 2 weeks after BM-Tx inflammatory grading, expression of inflammatory cell markers and associated chemokines and their receptors were increased and subsequently declined. In parallel, CD8+/GFP+ donor-derived T cells infiltrated the liver 2 weeks after BM-Tx. The Th1 cyokine interferon γ was increased 2 and 10 weeks after BM-Tx whereas the Th2 associated interleukin 13 was not altered. The gene expression of matrix metalloproteinases MMP-2, MMP-7, MMP-9 and MMP-13 was transiently upregulated and MMP-9 protein remained elevated 20 weeks after BM-Tx with enhanced gelatinase activity located within the fibrotic areas. Neutrophils were identified as major sources of MMP-9. Conclusion: These results show that BM-Tx causes an antifibrotic Th1 response combined with transient inflammatory effects and subsequently upregulated MMP activity. Antifibrotic Th polarisation and prolonged proteolytic activity, especially of MMP-9, might be responsible for long-term amelioration of hepatic fibrosis.